Variation in mesopelagic fish community composition and structure between Mediterranean and Atlantic waters around the Iberian Peninsula - Olivar, M. Pilar; Castellón, Arturo; Sabatés, Ana; Sarmiento-Lezcano, Airam; Emelianov, Mikhail; Bernal, Ainhoa; Yang, Yang; Proud, Roland; Brierley, Andrew S. (Frontiers in Marine Science, 2022)
We report variability in communities of mesopelagic fish between five zones around the Iberian Peninsula, i.e. Balears and Alboran in the western Mediterranean, and Cadiz, Lisboa and Galicia in the eastern Atlantic. Day and night samples were collected from 7 layers of the water column with a midwater trawl fitted with a multisampler. Temperature and salinity regimes were very different on the Mediterranean and Atlantic sides of the peninsula, with much higher values through the entire water column in the Mediterranean, characterized by a strong pycnocline. The highest productivity was observed off Lisboa, where Chlorophyll a concentrations were two orders of magnitude higher than in any other zone. The two zones visited in the western Mediterranean held 22 fish species, while 67 were found in the Atlantic. The lowest diversity and the highest dominance were observed in Balears, and the highest diversity was found in Cadiz zone. In all zones, but particularly in those in the Mediterranean, mesopelagic populations were dominated by a high number of small fish with low individual biomasses. The species Benthosema glaciale, Cyclothone pygmaea and Ceratoscopelus maderensis were common in the Mediterranean populations, whereas in the Atlantic, Cyclothone microdon/livida, Valenciennellus tripunctulatus, Ceratoscopelus. warmingii and Benthosema suborbitale were the most common species. Temperature and salinity (both at surface and in the mesopelagic zone) were the main environmental factors explaining variability in assemblage composition of mesopelagic fish during the survey. A persistent (day-night) deep scattering layer (DSL) was observed using the vessel-based echosounder in all zones, and was comprised primarily of the gonostomatid Cyclothone spp.. Night-time echosounder observations of scattering layers near the surface were observed in Balears, Alboran, Cadiz and Lisboa, where night surface net collections indicated that Myctophidae, Stomiidae and Phosichthyidae migration extended to the upper 100 m. Sternoptychids and the gonostomatid Sigmops elongatus seldom reached the upper 100 m in their night vertical migrations. Night stratified hauls of 30 m resolution carried out in the epipelagic zone showed that abundances maxima of migratory fish coincided with the location of the Chlorophyll a maxima.